1996
DOI: 10.1055/s-2007-1006461
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Facial Nerve Grafting for Facial Reanimation: Effect on Normal Hemiface Motion

Abstract: Reinnervation of the paralyzed hemiface with a cross-facial nerve graft (CFNG) required division of facial nerve branches on the normal hemiface to serve as axon donors. There is therefore concern about whether any impairment of normal hemiface motion occurs in the postoperative period. To minimize the likelihood of donor-side impairment, donor branches are chosen from the bucco-zygomatic region which was extensive cross branching, as opposed to be the single temporal or marginal mandibular branches. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…16 Careful selection of the donor branches of the normal facial nerve does not affect the function of the normal face. 17 Cross-facial nerve grafting can be used as well, to reinnervate a free muscle flap by direct coaptation with its motor nerve. A onestage procedure carries with it the danger of scarring at the distal coaptations on the paralyzed side.…”
Section: Discussionmentioning
confidence: 99%
“…16 Careful selection of the donor branches of the normal facial nerve does not affect the function of the normal face. 17 Cross-facial nerve grafting can be used as well, to reinnervate a free muscle flap by direct coaptation with its motor nerve. A onestage procedure carries with it the danger of scarring at the distal coaptations on the paralyzed side.…”
Section: Discussionmentioning
confidence: 99%
“…This is usually performed in two stages with a 3-6-month delay before stage 1 and a 9-12-month interval between stage 1 and stage 2. 1,11,46 Hence, the treatment strategy for human facial palsy sometimes includes partial or complete long-term denervation of the affected facial muscles. According to available data, denervated human facial muscles undergo substantial atrophic changes with time.…”
mentioning
confidence: 99%
“…Cooper et al 69 reported a series of seven patients with FP in whom the CFNG procedure was used for facial reanimation. According to that study, movement of the normal hemiface does not appear to be permanently affected by cross facial nerve graft when a careful choice of redundant bucco-zygomatic donor branches is made.…”
Section: Discussionmentioning
confidence: 99%